Implementation of Project Based Learning Independent Learning Curriculum in Japanese Speaking Skills - Stovia, Anggita; Kadafi, Muammar; Riyadi, Slamet (Journal of Japanese Language Education and Linguistics, 2025)
Students of Japanese Literature typically encounter challenges in verbalizing the Japanese language. Implementing an independent learning curriculum alongside the Project Based Learning model can facilitate students' proficiency in spoken Japanese, as it enables them to comprehend information, select themes, and actively engage in addressing their speaking challenges autonomously. This project, funded by LPPM Unsoed Skim project on Competency Improvement, aims to assess the enhancement of speaking skills among Japanese Literature students and identify the challenges they encounter. This study employs an experimental research methodology utilizing the One Group Pretest-Posttest Design. The tools employed for data collection include the speaking skills assessment rubric and interview instructions to identify speaking challenges. Data gathering methodologies encompass (1) oral assignment approaches, (2) observation, and (3) interviews. Qualitative observation data are evaluated utilizing the Miles and Huberman analytical framework, which encompasses data reduction, data display, and verification and conclusions. The study's results indicated that the speaking proficiency of Japanese Literature students who engaged in Project Based Learning surpassed that of their counterparts in conventional learning models, and the students' speaking challenges were identifiable.